Structural, spectral, thermal and dielectric properties of Nd-Ni co-doped Sr-Ba-Cu hexagonal ferrites synthesized via sol-gel auto-combustion route. Issue 1 (January 2018) - Malik, Huma; Khan, Muhammad Azhar; Hussain, Altaf; Warsi, Muhammad Farooq; Mahmood, Asif; Ramay, Shahid M.
Abstract: Neodymium-nickel (Nd-Ni) substituted nanocrystalline ferrites of the following chemical formula SrBaCu2−x Nix Ndy Fe12−y O22 (x = 0, 0.2, 0.4, 0.6, 0.8, 1.0, y = 0.0, 0.02, 0.04, 0.06, 0.08, 0.1) were synthesized by the sol-gel auto-combustion route. The synthesized samples were characterized by X-ray powder diffraction (XRD), thermogravimetric analysis (TGA), differential scanning calorimetry (DSC), fourier transform infrared spectroscopy (FTIR) and dielectric measurement techniques. The properties related to structure of the prepared samples were examined in detail in addition to thorough analysis of their dielectric properties. Microstructural studies exposed the formation of spherical, elongated grains and all the prepared samples showed single Y-type hexagonal phase and lattice parameters have been calculated. FTIR technique was employed to explore the local symmetry behavior in the synthesized crystalline materials and to probe the process of ordering in nano-crystalline ferrites. With increase in frequency and Nd-Ni contents, dielectric constant and dielectric loss of the samples was found to decrease. The complex impedance formalism confirms the role of grain-interior phenomenon to the dielectric properties. Resistive and capacitive characteristics of materials were exhibited by Cole-Cole plots having single semicircle, caused by contribution of grain boundaries in prepared Y-type nano materials.